E-Democracy and Citizen Participation in Liberia: Confronting the Challenges of Inclusivity and Engagement - Kerkulah P Nyeleker; Dian Eka Rahmawati; Eko Priyo Purnomo; Non Naprathansuk (Universitas Pancasakti Tegal, 2025)
E-democracy involves the idea that digital tools such as the Internet can enhance citizen participation in decision-making. However, Liberia, a post-conflict state, still faces challenges with e-democracy. This article explores the factors obstructing the realisation of e-democracy and its goal of fostering meaningful citizen engagement in Liberia. This study used a qualitative approach, collecting secondary data from peer-reviewed articles, official reports, newspapers, and other sources, and interactively analysed in the NVivo 12 Plus software. The analysis is based on Marianne Kneuer's theory of e-democracy, which comprises three indicators: free and equal access, e-participation, and e-government. The findings indicate that the implementation of e-democracy in Liberia encounters several obstacles: (i) limited free and unequal digital access due to weak legal protections for internet freedom, online intimidation, high internet costs, and low digital literacy; (ii) absence of e-participation as citizens struggle to access timely and reliable government information. Traditional media, especially radio, continues to be the primary source compared to digital platforms; (iii) lack of e-government services owing to ineffective online government platforms and unreliable digital services, which force citizens to rely on traditional methods to access public services.